Melanoma lymph node metastases – moving beyond quantity in clinical trial design and contemporary practice - Rhodin, Kristen E.; Fimbres, Denisse Porras; Burner, Danielle N.; Hollander, Shayna; O’Connor, Margaret H.; Beasley, Georgia M. (Frontiers in Oncology, 2022)
The presence of lymph node metastases is a well-studied prognostic factor for cutaneous melanoma. Characterization of melanoma lymph node metastases and their association with survival in multiple, large observational studies has led to recognition of the following high-risk features: quantity of lymph node metastases (number of nodes), size of the nodal tumor deposit (in mm), and extracapsular extension. Despite increasing utilization of these features in the design of randomized clinical trials, in addition to their role in contemporary clinical decision-making, current staging systems lag behind, only accounting for the quantity of lymph nodes with metastases. Herein, we review the prognostic role of melanoma lymph node metastases and their high-risk features, current reporting standards, how such features have been utilized in practice-changing trials, and best practices for future clinical trial design and clinical decision-making.